Grafting of PCL to EVA by reactive processing: effect of PCL molar mass - Moura, I. (2011)
Biobased graft copolymers, EVA-g-PCL, has been synthesized by transesterification reaction between EVA and PCL, using titanium propoxide Ti(OPr)4 as catalyser. The extent of the grafting reaction was estimated from the amount of copolymer extracted. Characterization of the copolymer formation was also performed using several analytical techniques, such as, SEM, TGA, DSC and XPS. Oxygen measurements were carried out to monitor the biodegradability of the prepared materials. The results obtained showed this method is an efficient way to enhance EVA biodegradability.